1985
DOI: 10.1176/ajp.142.7.840
|View full text |Cite
|
Sign up to set email alerts
|

Antithyroid antibodies in depressed patients

Abstract: The presence of antithyroid (antimicrosomal and antithyroglobulin) antibodies was assessed in 45 psychiatric inpatients with prominent depressive symptoms (28 with DSM-III major depression). Nine patients (20%) had detectable titers of antithyroid antibodies, a rate considerably higher than the 5%-10% observed in the normal population. Each of these nine patients with symptomless autoimmune thyroiditis had normal baseline serum thyrotropin concentrations and normal thyroid function (as assessed by T4, T3 uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…A prevalence of up to 20% of elevated titers of antithyroid antibodies has been documented in depressed patients in several reports compared to a 5–10% prevalence in the general population [4245]. However, this should be viewed with caution since these reports either lacked a control group [42, 43, 45] or showed no significant difference between the group with an affective disorder and the control group with a nonaffective psychiatric disorder [44].…”
Section: Antithyroid Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A prevalence of up to 20% of elevated titers of antithyroid antibodies has been documented in depressed patients in several reports compared to a 5–10% prevalence in the general population [4245]. However, this should be viewed with caution since these reports either lacked a control group [42, 43, 45] or showed no significant difference between the group with an affective disorder and the control group with a nonaffective psychiatric disorder [44].…”
Section: Antithyroid Antibodiesmentioning
confidence: 99%
“…However, this should be viewed with caution since these reports either lacked a control group [42, 43, 45] or showed no significant difference between the group with an affective disorder and the control group with a nonaffective psychiatric disorder [44]. Furthermore, whether this link may have any clinical significance remains unclear since it was most often accompanied by normal serum TSH concentrations [42, 43]. In addition, Fountoulakis et al found higher thyroid binding inhibitory immunoglobulins (TBII) in depressed patients suggesting the presence of an autoimmune process involving the thyroid gland in depressed patients [46].…”
Section: Antithyroid Antibodiesmentioning
confidence: 99%
“…Some cross-sectional studies found an association with depressive symptoms for both subclinical hypothyroidism [9,10] and subclinical hyperthyroidism [11]. Moreover, autoimmune thyroiditis, the most common cause of subclinical hypothyroidism among the elderly, has been shown to be more frequent in depressed patients than in healthy euthyroid individuals (20 vs. 5%) [12]. However, only few studies have prospectively compared euthyroidism with subclinical thyroid dysfunction and depression: two prospective studies found no association between subclinical hypothyroidism and depressive symptoms, but one of these included only the very elderly, all being aged 85 years and older [13], and another included only elderly men aged 70 years and older [14].…”
Section: Introductionmentioning
confidence: 99%
“…1 Since that time, there have been myriad reports of specific autoimmune responses to self-antigens in psychosis, affective dysregulation, and other behavioral abnormalities. 13 Despite these efforts, no autoantibody findings have remained so reproducible or ubiquitous as to become a biomarker for disease. 1,4 Recently, a number of syndromes characterized in part by global encephalopathy or even more focal psychiatric changes have been found to result from autoimmune dysfunction, at times with autoantibodies that guide both diagnosis and treatment.…”
mentioning
confidence: 99%